Atomic Vacancy Control and Elemental Substitution in a Monolayer Molybdenum Disulfide for High Performance Optoelectronic Device Arrays - Chee, Sang-Soo; Lee, Won-June; Jo, Yong-Ryun; Cho, Min Kyung; Chun, DongWon; Baik, Hionsuck; Kim, Bong-Joong; Yoon, Myung-Han; Lee, Kayoung; Ham, Moon-Ho (WILEY-V C H VERLAG GMBH, 2020)
Defect engineering of 2D transition metal dichalcogenides (TMDCs) is essential to modulate their optoelectrical functionalities, but there are only a few reports on defect-engineered TMDC device arrays. Herein, the atomic vacancy control and elemental substitution in a chemical vapor deposition (CVD)-grown molybdenum disulfide (MoS2) monolayer via mild photon irradiation under controlled atmospheres are reported. Raman spectroscopy, photoluminescence, X-ray, and ultraviolet photoelectron spectroscopy comprehensively demonstrate that the well-controlled photoactivation delicately modulates the sulfur-to-molybdenum ratio as well as the work function of a MoS2 monolayer. Furthermore, the atomic-resolution scanning transmission electron microscopy directly confirms that small portions (2-4 at% corresponding to the defect density of 4.6 x 10(12) to 9.2 x 10(13) cm(-2)) of sulfur vacancies and oxygen substituents are generated in the MoS2 while the overall atomic-scale structural integrity is well preserved. Electronic and optoelectronic device arrays are also realized using the defect-engineered CVD-grown MoS2, and it is further confirmed that the well-defined sulfur vacancies and oxygen substituents effectively give rise to the selective n- and p-doping in the MoS2, respectively, without the trade-off in device performance. In particular, low-percentage oxygen-doped MoS2 devices show outstanding optoelectrical performance, achieving a detectivity of approximate to 10(13) Jones and rise/decay times of 0.62 and 2.94 s, respectively.
Keywords: CHEMICAL-VAPOR-DEPOSITION; FEW-LAYER MOS2; PLASMA; PHOTODETECTOR; ENHANCEMENT; GROWTH